The relationship between age and parity with the incidence of hyperemesis gravidarum in pregnant women at inpatient puskesmas Kota Karang Bandar Lampung in 2020 - Psiari Kusuma Wardani; Mareza Yolanda Umar (Universitas Aisyah Pringsewu, 2023)
Hyperemesis gravidarum in pregnant women can be identified if pregnant women experience vomiting every time they eat and drink or in a day the mother experiences several vomiting and can also be accompanied by weight loss. The incidence of Hyperemesis Gravidarum according to the World Health Organization reaches 12.5% of all pregnancies in the world and in Indonesia reaches 14.8% of all pregnancies and in Lampung Province reaches 10-15%. Knowing the relationship between age and parity with the incidence of Hyperemesis Gravidarum in pregnant women at the Inpatient Puskesmas Kota Karang in 2021 is the aim of this study using quantitative research with a total population of all pregnant women in the working area of the Puskesmas Kota Karang in 2021 with a sample of 78 people use case control. prevalence of pregnant women experiencing Hyperemesis Gravidarum was 56.4%, the risk of experiencing Hyperemesis Gravidarum was due to the age factor of 57.7% and the parity at risk of experiencing Hyperemesis Gravidarum was 57.7% so that the relationship between age and parity with the incidence of Hyperemesis Gravidarium was obtained. in pregnant women at the Inpatient Puskesmas Kota Karang by showing a p value: 0.01 or less than 0.05. The results of this study are expected to be input for residents of kota karang, Teluk Betung Timur, kota Bandar Lampung regarding the prevention and treatment of hyperemesis gravidrum in pregnant women so that they can reduce the incidence of hyperemesis gravidaum. Abstrak: Hiperemesis gravidarum pada ibu hamil dapat diidentifikasikan apabila ibu hamil mengalami muntah pada setiap makan dan minum atau dalam sehari ibu mengalami beberapa kali muntah dan dapat juga disertai dengan penurunan berat badan. Angka kejadian hiperemesis gravidarum (HEG) menurut WHO sebesar 12,5% dari jumlah seluruh ibu hamil dan di Indonesia mencapai 14,8% dari seluruh kehamilan serta pada Provinsi Lampung mencapai 10-15%. Mengetahui hubungan usia dan paritas dengan kejadian hiperemesis gravidarum pada ibu hamil di Puskesmas Rawat Inap Kota Karang tahun 2021 adalah tujuan dari penelitian ini dengan menggunakan penelitian kuantitatif dengan jumlah populasi adalah seluruh ibu hamil di wilayah kerja Puskesmas Rawat Inap Kota karang Tahun 2021 dengan sampel berjumlah 78 orang menggunakan case control. Hasil penelitian diperoleh prevalensi kejadian ibu hamil mengalami hiperemesis gravidarum sebanyak 56,4%, berisiko mengalami kejadian hiperemesis gravidarum karna faktor usia sebanyak 57,7% serta paritas beresiko mengalami hiperemesis gravidarium ialah 57,7% sehingga didapatkan hubungan usia dan paritas dengan kejadian hiperemesis gravidarium pada ibu hamil di Puskesmas Rawat Inap Kota Karang dengan menunjukkan nilai p value: 0,01 atau kurang dari 0,05. Hasil penelitian ini diharapkan dapat menjadi masukan bagi warga Kota Karang Kecamatan Teluk Betung Timur Kabupaten Bandar Lampung tentang pencegahan dan penanganan hiperemesis gravidarum pada ibu hamil sehingga dapat menekan angka kejadian hiperemesis gravidaum.